Differential inhibition of membrane type 3 (MT3)-matrix metalloproteinase (MMP) and MT1-MMP by tissue inhibitor of metalloproteinase (TIMP)-2 and TIMP-3 rgulates pro-MMP-2 activation. - Zhao, H; Bernardo, M; Osenkowski, P; Sohail, A; Pei, D; Nagase, H; Kashiwagi, M; Soloway, P; DeClerck, Y; Fridman, R (2004)
The membrane type (MT)-matrix metalloproteinases (MMPs) constitute a subgroup of membrane-anchored MMPs that are major mediators of pericellular proteolysis and physiological activators of pro-MMP-2. The MT-MMPs also exhibit differential inhibition by members of the tissue inhibitor of metalloproteinase (TIMP) family. Here we investigated the processing, catalytic activity, and TIMP inhibition of MT3-MMP (MMP-16). Inhibitor profile and mutant enzyme studies indicated that MT3-MMP is regulated on the cell surface by autocatalytic processing and ectodomain shedding. Inhibition kinetic studies showed that TIMP-3 is a high affinity inhibitor of MT3-MMP when compared with MT1-MMP (K(i) = 0.008 nm for MT3-MMP versus K(i) = 0.16 nm for MT1-MMP). In contrast, TIMP-2 is a better inhibitor of MT1-MMP. MT3-MMP requires TIMP-2 to accomplish full pro-MMP-2 activation and this process is enhanced in marimastatpretreated cells, consistent with regulation of active enzyme turnover by synthetic MMP inhibitors. TIMP-3 also enhances the activation of pro-MMP-2 by MT3-MMP but not by MT1-MMP. TIMP-4, in contrast, cannot support pro-MMP-2 activation with either enzyme. Affinity chromatography experiments demonstrated that pro-MMP-2 can assemble trimolecular complexes with a catalytic domain of MT3-MMP and TIMP-2 or TIMP-3 suggesting that pro-MMP-2 activation by MT3-MMP involves ternary complex formation on the cell surface. These results demonstrate that TIMP-3 is a major regulator of MT3-MMP activity and further underscores the unique interactions of TIMPs with MT-MMPs in the control of pericellular proteolysis.